Performance characterisation of a seperated heat-pipe-heat-recovery-heat-exchanger for the food drying industry - Thomas, Nathan Shane (Stellenbosch : Stellenbosch University, 2016)
Thesis (MEng)--Stellenbosch University, 2016.